Antifeedant and repellent activities of Melia azedarach L. fruit extracts on fall armyworm - Scapinello, Jaqueline; de Oliveira, J. Vladimir; Kuhn, Fernanda; Albeny-Simões, Daniel; Chiaradia, Luis; Tomazelli Jr., Osmar; Dalmagro, Jacir (Acta Scientiae et Technicae; v. 4 n. 1 (2016)DO - 10.17648/uezo-ast-v4i1.123, 2016)
The aim of this study was to evaluate the appetite suppression and insecticidal activity of Melia azedarach aerial component extracts on the larvae of Spodoptera frugiperda obtained from the maceration by solvent, ultrasound and supercritical CO 2 extraction. Extracts of aerial components of M. azedarach were obtained by three different extraction methods (maceration, ultrasound and supercritical extraction) using different solvents (ethanol, n-hexane, ethyl acetate and CO 2 ) for use in testing appetite suppression activity in S.  frugiperda (Lepidoptera: Noctuidae). Extracts were sprayed on third instar larvae, which were then placed on corn seedlings. Extracts prepared by ethanol maceration of the fruits and branches showed appetite suppression and repellent activity, extracts of fruits obtained with n-hexane solvent and supercritical CO 2   resulted in significantly reduced leaf damage in the corn, with a result equivalent to the positive control (commercial insecticide). Regarding larvae mortality, the supercritical CO 2 extract of fruits resulted in the highest S. frugiperda mortality among the tested extracts, equivalent to treatment with positive control. This extract appears to be the most promising for controlling this corn crop insect pest.